Yield response of mulched field grown tomatoes irrigated with carbonated water - Novero, Ricardo Pegenia, author; Moore, Frank D., III, advisor; Towill, Leigh E., committee member; Shanahan, John F., committee member; Smith, D. D., committee member (Colorado State University. Libraries, 1991)
Hundreds of literature citations report positive responses of crops to CO2 enrichment of greenhouse atmospheres. Carbon dioxide enrichment was done, either by open air fumigation with CO2 gas or irrigation with carbonated water. In the open field where wind movement deters CO2 enrichment, open air fumigation techniques were mostly a failure and the benefits of irrigation with carbonated water to plants has yet to be established. The response of mulched field-grown tomatoes to irrigation with carbonated water using drip irrigation system was studied during 1988 and 1989. Injecting CO2 into the irrigation water decreased water pH and, consequently, lowered soil pH. The decrease in soil pH, which was expected to increase the availability of P, Ca, and metallic elements such as Zn, Fe, and Mn, did not affect the plant uptake of any of the aforementioned elements except for Zn. Zinc concentration in the leaves of CO2 treated plants was higher than that of the control plants for the 1988 experiment. Above ground enrichment at the crop canopy level was evident primarily during irrigation. However, residual soil CO2 was observed for the mulched plots irrigated with carbonated water. Soil CO2 concentrations for the control and carbonated water treated plots were similar under unmulched conditions. Mulching alone increased fruit yield by 8%, and further yield increases ranging from 7 to 23% were attributed to irrigation with carbonated water. The yield component contributing most to increased fruit yield in plots irrigated with carbonated water was fruit size. The observed yield increase for carbonated water irrigated plants was probably due to enhancement of photosynthesis. Plants treated with carbonated water produced fruits with higher soluble solids, a quality factor that may be preferred.
Covers not scanned.
Keywords: Tomatoes; Mulching